Armenia : Workforce Development - World Bank (Washington, DC, 2015)
Armenia has made considerable efforts to reinforce its education and training systems' capacity to respond to the pressures of globalization and the challenges of a knowledge-based economy. This report presents a comprehensive diagnostic of the country's workforce development (WfD) policies and institutions to inform policy dialogue on this important issue. The results are based on a new World Bank tool designed for this purpose. SABER-WfD, the tool is part of the World Bank's initiative on systems approach for better education results (SABER), the aim of which is to provide systematic documentation and assessment of the policy and institutional factors that influence the performance of education and training systems. It examines three crucial dimensions of the WfD system: strategic framework, system oversight, and service delivery. The SABER-WfD tool encompasses initial, continuing, and targeted vocational education and training that are offered through multiple channels and focuses largely on programs at the secondary and post-secondary levels. This report documents the results of the use of the SABER-WfD tool in Armenia for the first time. A key trend is that while the WfD system is producing an increasingly highly educated workforce, graduates do not possess the specific skills required by the labor market, which are often lower-level skills and attainable through shorter periods of education. Therefore, it is important to continue with the system reforms that aim to increase the quality of professional education and to bring it into compliance with labor market demands as well as the strategic educational and development objectives of the country.